Manipulation of Root Growth in Carrot (Daucus carota) cv. Nantes through Foliar Application of GA3 - , Jeenia Thalyari; , Manish Kumar; , Sparsh Madaik (Archives of Current Research International, 2025)
Thin roots with uniform size from top to bottom are preferred for slicing and canning throughout the world. Nantes-type carrots are characterized by their cylindrical shape and nearly same diameter from end to end. The ability of GA3 to alter root diameter and hence increase its suitability for slicing was studied in carrot cv. Nantes over the course of two consecutive growing seasons during 2021-22 and 2022-23 at Dr Yashwant Singh Parmar University of Horticulture and Forestry Nauni, Solan, Himachal Pradesh. Three concentrations of GA3 i.e. 100, 150 and 200 ppm were sprayed onto 6 week old carrot seedlings. GA3 sprays applied to carrot plants stimulated shoot growth and inhibited root growth. Maximum reduction in root diameter and root weight was observed in carrot plants sprayed with 200 ppm GA3 but the reduction in root size was up to a point where they were still suitable for processing and slicing.